Σχεδιασμός φορητής συσκευής αναπαραγωγής ήχου (για την παραγωγή της με καλούπια) : - Κωτσοπούλου, Ματίνα-Ασπασία (2009)
Σχεδιασμός φορητής συσκευής αναπαραγωγής ήχου (για την παραγωγή της με καλούπια)